A Study On The Sexual Harassment Of Transgender Persons With Special Reference To Their Mental Wellbeing In Production Industries - Ms. Krupa Dipakkumar Shah; Dr. Suja Nayar; Ms. Senali Trivedi; Ms. Jeni Nandkumar Adhyaru; Ms. Urvashi Sharma (Revista Electronica de Veterinaria, 2024)
India is marking its success in all spheres with most inclusivity and is marching towards achieving gender neutrality. However, it was only in 2014, when Indian Judiciary in a remarkable judgement recognised transgender as third gender, entrusting them with all fundamental rights at par with cis-gender people. In the current era, India is coming forward strongest then ever when it comes to Economy. Though, to make India largest and strongest economy, participation of people belonging to all genders is very much anticipated. More people belonging to third gender are joining the workforce contributing to the economic success of India. Although, when it comes to sexual harassment at workplace, third gender are considered to be most marginalised community which requires protection of law. The aim of the research paper is to study the scope of ‘The Sexual Harassment of Women at Workplace (Prevention, Prohibition and Redressal) Act, 2013’ with special reference to inclusivity of transgender people in general and trans-women in specific, to promote mental wellbeing for them in the Production Industries like Biofuel, Textile, Recycle Industries etc. The article studies the provisions of the Act and concludes that in absence of specific definition of the term ‘women’ as enumerated in the POSH Act, it can be inferred that the definition includes both cis-women and trans-women within its purview. The article further advocates for making the POSH Act gender neutral providing protection, both sexually and mentally, to people belonging to all genders.